And then there were crumbs - Calder, Eve (Calder, Eve. Cookie House mystery., 2019)
Kate McGuire<U+2019>s life was sweet in Manhattan before she lost her restaurant job and fiancé both. But sometimes that<U+2019>s just the way the cookie crumbles, and soon she finds herself starting from scratch in the island town of Coral Cay, Florida. It has everything she<U+2019>s looking for: sunny beaches, friendly locals, and a Help Wanted sign in the bakery shop window. Once she convinces the shop<U+2019>s crusty owner Sam Hepplewhite to hire her, Kate can<U+2019>t tie on her apron fast enough. Little does she know that trouble, like warm dough, is on the rise. . . Stewart Lord is a real estate developer with a taste for a different type of dough: the green kind. He knows that he could make a killing by purchasing the Cookie House from Sam, who flat-out refuses to sell. But when Stewart turns up the heat on Sam<U+2015>then turns up dead after eating a fresh batch of Sam<U+2019>s cinnamon rolls<U+2015>all eyes focus on the town<U+2019>s beloved bakery. When the police arrest Sam for murder, Kate must somehow prove that her curmudgeonly boss is innocent. Enlisting the help of a team of lovable locals, Kate sets out to catch the real culprit with his hand in the cookie jar<U+2026>before someone else gets burned.